Development of an online, universal, Utstein registry‐based, care practice report card to improve out‐of‐hospital resuscitation practices. Issue 2 (22nd January 2018) - Baert, Valentine; Escutnaire, Joséphine; Nehme, Ziad; Mols, Pierre; Lagadec, Steven; Vilhelm, Christian; Jacob, Line; Wiel, Eric; Adnet, Frédéric; Hubert, Hervé; ,
Abstract: Rationale, aims and objectives: Care quality is a primary concern in health field. In France, the care practice report card (CPRC) is compulsory for practitioners. It is the first step towards the culture of excellence. In this context, practitioners have to assess and improve their practices. Competent authorities define registries as reliable sources for CPRC. The first aim of this work is to describe how we designed and built a universally transposable CPRC model based on an Utstein‐style cardiac arrest registry. The second aim is to measure the adherence of practitioners to this approach and to show how such a tool can be used in real situation. Methods: Our report card is adapted from in‐hospital CA care quality and safety indicators. We built a 2‐section grid. The first part described the quality and completeness of the analysed data. The second part distinguished medical and traumatic CA and assesses care practices. We analysed the practitioners' adherence thanks to a satisfaction survey. Finally, we presented a CPRC case study. Results: This tool was tested in 92 centres gathering 8433 patients. The satisfaction survey showed that this CPRC was well accepted by emergency professionals. We presented an implementation example of this tool in a centre in real‐life situation. Conclusions: We designed and implemented a fully automated CPRC tool routinely usable for Utstein‐style CA registries. This CPRC is easily transferable in all other Utstein CA registries. The debriefing report source codes are freely distributed upon request. This tool enables the care assessment and improvement.